One-year Results of the Effects of Rituximab on Acute Antibody-Mediated Rejection in Renal Transplantation: RITUX ERAH, a Multicenter Double-blind Randomized Placebo-controlled Trial. Issue 2 (February 2016) - Sautenet, Bénédicte; Blancho, Gilles; Büchler, Mathias; Morelon, Emmanuel; Toupance, Olivier; Barrou, Benoit; Ducloux, Didier; Chatelet, Valérie; Moulin, Bruno; Freguin, Caroline; Hazzan, Marc; Lang, Philippe; et al.
Abstract : Background: Treatment of acute antibody-mediated rejection (AMR) is based on a combination of plasma exchange (PE), IVIg, corticosteroids (CS), and rituximab, but the place of rituximab is not clearly specified in the absence of randomized trials. Methods: In this phase III, multicenter, double-blind, placebo-controlled trial, we randomly assigned patients with biopsy-proven AMR to receive rituximab (375 mg/m 2 ) or placebo at day 5. All patients received PE, IVIg, and CS. The primary endpoint was a composite of graft loss or no improvement in renal function at day 12. Results: Among the 38 patients included, at 1 year, no deaths occurred, but 1 graft loss occurred in each group. The primary endpoint frequency was 52.6% (10/19) and 57.9% (11/19) in the rituximab and placebo groups, respectively ( P = 0.744). Renal function improved in both groups, as soon as day 12 with no difference in serum creatinine level and proteinuria at 1, 3, 6, and 12 months. Supplementary administration of rituximab and total number of IVIg and PE treatments did not differ between the 2 groups. Both groups showed improved histological features of AMR and Banff scores at 1 and 6 months, with no significant difference between groups but with a trend in favor of the rituximab group. Both groups showed decreased mean fluorescence intensity of donor-specific antibodies as soon as day 12, with no significant difference between them but with a trend in favor of the rituximab group at 12 months. Conclusions: After 1 year of follow-up, we observed no additional effect of rituximab in patients receiving PE, IVIg, and CS for AMR. Nevertheless, our study was underpowered and important differences between groups may have been missed. Complementary trials with long-term follow-up are needed. Abstract : Supplemental digital content is available in the text.